Expression of p53 in leukoplakia and squamous cell carcinoma of the oral mucosa: correlation with expression of Ki67. Issue 3 (June 1996) - Kannan, S; Chandran, G Jagadeesh; Pillai, K Raveendran; Mathew, Babu; Sujathan, K; Nalinakumary, K R; Nair, M Krishnan
Abstract : Aim —To study p53 expression in relation to proliferative status in normal and nondysplastic, dysplastic and malignant lesions of the oral mucosa. Method —The standard avidin-biotin complex (ABC) immunohistochemical staining method was used to study the expression of p53 and Ki67 on frozen sections of oral leukoplakias and carcinomas. Results —Of the leukoplakia and carcinoma samples, 70% expressed p53 in over 5% of cells. In normal mucosa less than 5% of cells expressed p53. The proliferation index, as assessed by expression of Ki67, was highest in the malignant lesions (43%) and lowest in normal mucosa (11%). Statistical analysis revealed that expression of both p53 and Ki67 was correlated significantly with the histopathological stage of the tumour. However, expression of p53 was not correlated with that of Ki67. In leukoplakia lesions with proliferative features p53 immunostaining was less intense than in non-proliferative lesions; this difference was statistically significant. Conclusions —These results emphasise the potential of Ki67 and p53 as biomarkers of carcinogenesis in oral cancer and may also serve as intermediate points for cancer prevention programmes, such as the oral chemopreventive trials. Factors other than p53 may have a more important role in the deregulation of proliferation in pre-malignant oral lesions.